The pH-electrodeposition-dependant of Iron Oxide Toward The Physicochemical Characteristics and Electrochemical Performance in Biorefractory Pollutant Degradation - Kosimaningrum, Widya Ernayati; Heriyanto, Heri; Yulvianti, Meri; Pitaloka, Alia Badra; Najahtama, Muhammad Raja; Wibisana, Muhammad Aditya; Sutianingsih, Yulis (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2023)
Electrodeposition of the iron oxide (FexOy) nanoparticles on the graphite felt was prepared from a mixture of iron (II) and iron (III) precursor solution with various pHs (2, 7, and 10) by applying a constant current (galvanostatic) of 0.1 A for 30 minutes. Each resulting sample was coded GF/FexOy -2, GF/FexOy -7, and GF/FexOy -10, respectively. Graphite felt without modification, Raw-GF, was used as control. The mass of iron oxide (FexOy) deposited ranged from 0.02 to 0.03 grams. The product characterisation using a Scanning Electron Microscope (SEM) showed the distribution of 500 nm particles on the surface of the graphite felt for the GF/FexOy -2 sample. In comparison, the distribution of larger particles (1 – 2 μm) was observed in the samples of GF/FexOy -7 and GF/FexOy -10, respectively. Spectrum resulting from an X-ray Diffraction Spectroscopy (XRD) showed the formation of iron oxides (FexOy) such as magnetite (Fe3O4), haematite (Fe2O3), goethite (FeOOH), and lepidocrocite (FeO(OH)). Fourier Transform Infra-Red (FTIR) spectrum also confirmed the presence of Fe2O3 in the GF/FexOy -2 sample, Fe3O4 in the GF/FexOy -7 and GF/FexOy -10 samples, and FeOOH in all three samples. Applying the iron oxide modified graphite felt in the electro-Fenton approach process without aeration showed that it can degrade bio-refractory pollutants, such as methyl orange. The observed degradations of methyl orange were a decrease in the colour intensity up to 81.37% and a decrease in the COD up to 49.85%.